Моделі споживчої поведінки киян і модернізація міського способу життя в УРСР 1955–1965 рр. - Борисенко, М. (Український історичний журнал, 2021)
Розвідка присвячена маловідомій у сучасній українській історіографії проблемі –
моделям споживчої поведінки радянських громадян. Мета статті – сформувати власну
дослідницьку концепцію змін у повсякденному житті міського населення середини ХХ ст.
Методологія, джерела. Застосовано етнографічний підхід для визначення стратегій
споживання, якими користувалися мешканці УРСР. Основним джерелом вивчення
порушеного питання стали інтерв’ю киян та архівні матеріали. Ґлобальна модернізація, яка
розпочалася в Північній Америці та Західній Європі в 1950-х рр., кардинально змінила
світ. Зміни ці мали широкий характер, охоплюючи політичне життя, культуру, повсякдення,
технології, соціальну структуру. Новий спосіб життя, культурні практики стали доступними
для багатьох людей у всьому світі. Автор ставить питання, чи був цей процес характерний для
СРСР і як комуністичний режим вплинув на модернізацію повсякденного життя українців у
1950–1960-х рр. Наукова новизна полягає у формулюванні окресленої проблеми та спробі
її вирішення. У висновках стверджується, що радянська торгівля копіювала європейські
й американські підходи до роздрібної сфери, але мала свої суперечності, адже споживачі
залишалися наодинці між пропаґандистським образом суспільства процвітання й реальним
товарним дефіцитом. Поміж цими полярними позиціями в містах сформувалася унікальна
культура самозабезпечення радянських людей. This article exam unfamiliar in the modern Ukrainian historiography issue is a
consumer behavior of soviet citizens. The purpose of the article is a foundation a research
concept of changes in the daily life of the urban population in the middle of the twentieth
century. Methodology and research data. It is undeniable, that society got a new impulse for
development during this period. This statement has formed a number of different methodological
approaches and theories that interpreted society after the World War II. One of them is the theory
of modernization, which is supported by the author of the article. The author uses an ethnographic
approach to determine the consumption strategies used by the citizens of UkrSSR in the second
half of the 20th century. In-depth interviews with Kyiv residents are the main source for the study of
this issue. The global modernizations that had began in North America and Western Europe in the
1950s changed our world dramatically. These changes were very broad in nature, embrace political
life, culture, ordinary life, technology, and the social structure of the population. The new way of
life became available to many people and cultural practices became common to people through the
world. The author of the article asks: is that process was appropriated of the USSR and how did
the communist regime influenced the modernization of everyday life of Ukrainians in 1950–1960?
The foundation and continues attempt to solve this issue is a novelty of current research. It is
concluded, that Soviet trade was copied European and American patterns of approaches for retail,
but was contradictory. Soviet consumers were left between the propaganda image of a society of
prosperity and the trade deficit. Between these polar extremes, a unique culture of life-support of
the Soviet people in the cities was formed, which is reflected in this article.